MENINGKATKAN NILAI AFEKTIF DAN HASIL BELAJAR MATERI NATURAL PHENOMENA MELALUI MODEL SCIENTIFIC INQUIRY - Kartika, Aprilia Indra; Pukan, Krispinus Kedati; Mustikaningtyas, Dewi (Journal of Biology Education, 2014)
Application measures of inquiry conducted by teachers who do not meet the basic standards, so that students have trouble doing scientific work skills well. Teachers had not found the right method for learning the material Natural Phenomena. In addition, teachers do not monitor students affective value in a sustainable manner, while the affective value determines the success of student learning. This study aimed to analyze the application of scientific inquiry teaching model can improve student affective value and learning outcomes class VII in SMP N 2 Semarang. This research was classroom action research which consisted of 3 cycles of learning. The sample in this research were class VII D and VII E. Results of the analysis of students affective learning value showed the average scientific interests and attitudes of students in learning increases in each cycle. Average learning outcomes student of class VII D and VII E on the first cycle of 46,32; second cycle of 49,63; and the third cycle 82,81. Conclusions from this research was the application of scientific inquiry teaching model can increase the value of affective and cognitive learning outcomes matter Natural Phenomena class VII D and E in the Junior High School 2 Semarang Penerapan langkah-langkah inkuiri yang dilakukan oleh guru tidak memenuhi standar yang baku, sehingga siswa kesulitan melakukan ketrampilan bekerja ilmiah dengan baik. Guru belum menemukan metode yang tepat untuk pembelajaran materi Natural Phenomena. Selain itu, guru belum memantau nilai afektif siswa secara berkelanjutan, sedangkan nilai afektif menentukan keberhasilan belajar siswa. Tujuan penelitian ini adalah analisis penerapan model pembelajaran scientific inquiry untuk meningkatkan kemampuan afektif dan hasil belajar siswa kelas VII di SMP N 2 Semarang. Penelitian ini merupakan penelitian tindakan kelas dengan kolaborasi antara guru dengan mahasiswa yang terdiri dari 3 siklus pembelajaran. Sampel dalam penelitian ini yaitu kelas VII D dan VII E. Hasil analisis nilai afektif siswa terhadap pembelajaran menunjukkan rata-rata minat dan sikap ilmiah siswa dalam pembelajaran meningkat di setiap siklusnya. Rata-rata hasil belajar siswa kelas VII D dan VII E pada siklus I sebesar 46,32; siklus II 49,63; dan siklus III 82,81. Simpulan dari penelitian ini adalah penerapan model pembelajaran scientific inquiry dapat meningkatkan nilai afektif dan hasil belajar kognitif materi Natural Phenomena siswa kelas VII D dan E di SMP Negeri 2 Semarang.